Driving Factors for Torrential Mass-Movements Occurrence in the Western Alps - Tiranti, Davide; Cremonini, Roberto; Asprea, Irene; Marco, Federica (Frontiers in Earth Science, 2016)
To understand the behaviour of torrential processes in the alpine environment, the conditions mainly responsiblefor the occurrence of these phenomena have to be identified and distinguished(classified) aspredisposing and triggering factors. In this regard, this study is aimed to understanding which factors lead to the occurrence of a given torrential processes in alpine catchments in the Western Alps, where information on past events are exhaustive and characterized by a long historical series. More than 769 documented torrential eventsoccurred from 1728 to 2015 within 78 catchments. Datasets concerning climate, geology and morphology, land use and the presence of historical landslide activity have been elaborated as input for multivariate statistical analysis to characterize the behaviour of the catchments. The results pinpoint the factors that mainly drive the type of torrential dominant process occurring in a given catchment, its occurrence probability, and its frequency. This study has demonstrated that catchments characterized by a significant percentage of outcropping rocks show a greater occurrence of torrential processes, especially hyperconcentrated flows and debris flows; on the contrary highly vegetated catchments are typically subject to water flows. This result can be a useful tool for the evaluation of hazards related to this specific phenomenon, making it possible to predict the most likely torrential processes that can be generated in a specific basin, given the characteristics of outcropping rock and vegetation cover.